Using Blended Learning to Support Students Thinking Powers in Multivariable Culculus - Kashefia, Hamidreza; Ismail, Zaleha; Mohammad Yusof, Yudariah (Sains Humanika, 2011)
Promoting mathematical thinking plays a significant role in the learning of advanced mathematics. Researchers usually try to support the students to overcome their difficulties in multivariable calculus by promoting mathematical thinking. The literature review and our preliminary study reveal that there are still certain difficulties faced by students when they adopt the new mathematical ideas and objects in multivariable calculus through mathematical thinking approach. In this paper, the theoretical framework for promoting mathematical thinking by computer has been discussed and theoretical reasons for selecting blended learning for promoting mathematical thinking in multivariable calculus have been put forward. Blended learning by integration of the benefits of both face-to-face and computer environments have been suggested as a relevant environment to help students in the learning of multivariable calculus through mathematical thinking approach.